Analysis of the Relationship between Macronutrients and Components of Physical Conditions in Amateur Aerobic Gymnastics - Erniwati Erniwati; Mohammad Arif Ali; Dewi Marfu’ah Kurniawati; Gustiana Mega Anggita (JUARA : Jurnal Olahraga, 2022)
This study aimed to determine the relationship between macronutrients and the main physical conditions of amateur aerobic gymnasts. This is quantitative descriptive research with data analysis using a bivariate correlation test. This study sample comprised 15 people who met the inclusion criteria. This research was conducted in the Cempaka Obic Lovers gymnastics community, Cempaka Village, Cirebon Regency. This research instrument uses a food record form survey method for 7x24 hours and a physical condition test which includes a cardiorespiratory endurance test, a coordination test and a reaction speed test. The results of this study stated that the average age of the respondents was 25±3.80 years, carbohydrates 564.41±139.96 kcal, fat 418.45±108.93 kcal, protein 182.80±42.55 kcal, cardiorespiratory energy resistance 22.53±1.30 mL/Kg/min, coordination 18.80±1.97 points and reaction rate 15.08±4.10 cm. Carbohydrate, fat, and protein intake on the physical condition of cardiorespiratory endurance, coordination, and reaction speed did not have a significant relationship (p>0.05). The conclusion of this study states that there is no important relationship between macronutrients consisting of carbohydrates, fats and proteins with the components of the physical condition of cardiorespiratory endurance, coordination and reaction speed of amateur aerobic gymnasts.